PENGARUH TINGKAT PENDIDIKAN PEMILIK, SKALA USAHA, UMUR USAHA TERHADAP PEMANFAATAN INFORMASI KEUANGAN - Febriyanti, Ariska Tri; Puspitaningtyas, Zarah; Prakoso, Aryo (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112)DO - 10.24843/bse.2017.v22.i01.p10, 2017)
The Influence of Owner’s Education Level, Business Scale, Business Age Toward The Utilization of Financial Information. The aim of this research is to identify the the influence of owner’s education level, business scale, business age toward the utilization of financial information of the small and medium business in Jember district (empirical study of restaurants and food houses). This research is done by distributing questionnaires to restaurants and food houses’ owner as much as 30 owners. The data analysis technique used in this study is multiple linear regression analysis. The result of this research shows that the owner’s education level has significant effect toward utilization of financial information of the small and medium business in Jember district (empirical study of restaurants and food houses).